Pengaruh Kualitas Produk, Harga, Dan Sertifikasi Halal Terhadap Keputusan Pembelian Naavagreen Skin Care Di Kota Malang - Ayu Novita Permatasari; Rois Arifin; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this research is to find out and analyze how the effect of Product Quality, Price, and Halal Certification on the Purchase Decision of Naavagreen Skin Care in Malang City. The population used in this study were Medical Students who used Naavagreen Skin Care. The sampling technique used in this research is purposive sampling. The variables in this study are Product Quality, Price, Halal Certification and Purchase Decision. The results of this study explain that the variables of Product Quality, Price, and Halal Certification have a significant effect on purchasing decisions simultaneously. Product Quality has a significant effect on Purchase Decisions, and Halal Certification has a significant effect on Purchase Decisions. Keywords: Product Quality, Price, Halal Certification, Purchase Decision